Semiotika Sosial Teks “I Cupak Teken I Gerantang Ddengan Konsep Tri Hita Karana: Kajian Linguistik Sistemik Fungsional - Suardana, I Ketut; Yoga Putra Semadi (Humanis, 2026)
Text of “I Cupak Tekȇn I Gerantang” is one of narrative texts which is very popular in Balinese communities. The text embeds symbolic meaning which has not been understood yet by a lot of Balinese communities comprehensively.  This research would like to explore the philosophy of the text associated with Tri Hita Karana. This research employs qualitative, Grounded Theory.  The theory used to explore the social phenomenon is the theory of Systemic Functional Linguistics (SFL). The data source used for this research is from Balinese folktale collection written by Suwija et al. The clauses were analyzed with SFL theory, namely; context of situation, context of culture, and ideology. The result of this research indicates that the text teaches us how to use appropriate language in accordance with the principle of Tri Hita Karana, namely; good language use will make harmonies for the users and the environment, good language use brings positive impact for the users and the others, good language use is the representation of God teaching. The text teaches us how to behave by emphasizing aesthetic, and ethic to all communities. This research gives positive impacts for applied linguistics development especially SFL and Semiotics. This result of the research can enrich applied linguistic references which can be used for the following linguistics researches.